Molecular Markers for Granulovacuolar Degeneration Are Present in Rimmed Vacuoles - Nakamori, Masahiro; Takahashi, Tetsuya; Nishikawa, Tomokazu; Yamazaki, Yu; Kurashige, Takashi; Maruyama, Hirofumi; Arihiro, Koji; Matsumoto, Masayasu (PloS one, 2013)
Rimmed vacuoles (RVs) are round-oval cytoplasmic inclusions, detected in muscle cells of patients with myopathies, such as inclusion body myositis (IBM) and distal myopathy with RVs (DMRV). Granulovacuolar degeneration (GVD) bodies are spherical vacuoles containing argentophilic and hematoxyphilic granules, and are one of the pathological hallmarks commonly found in hippocampal pyramidal neurons of patients with aging-related neurodegenerative diseases, such as Alzheimer's disease and Parkinson's disease. These diseases are common in the elderly and share some pathological features. Therefore, we hypothesized that mechanisms of vacuolar formation in RVs and GVD bodies are common despite their role in two differing pathologies. We explored the components of RVs by immunohistochemistry, using antibodies for GVD markers. Subjects included one AD case, eight cases of sporadic IBM, and three cases of DMRV. We compared immunoreactivity and staining patterns for GVD markers. These markers included: (1) tau-modifying proteins (caspase 3, cyclin-dependent kinase 5 [CDK5], casein kinase 1δ [CK1δ], and c-jun N-terminal kinase [JNK]), (2) lipid raft-associated materials (annexin 2, leucine-rich repeat kinase 2 [LRRK2], and flotillin-1), and (3) other markers (charged multi-vesicular body protein 2B [CHMP2B] and phosphorylated transactive response DNA binding protein-43 [pTDP43]) in both GVD bodies and RVs. Furthermore, we performed double staining of each GVD marker with pTDP43 to verify the co-localization. GVD markers, including lipid raft-associated proteins and tau kinases, were detected in RVs. CHMP2B, pTDP43, caspase 3, LRRK2, annexin 2 and flotillin-1 were detected on the rim and were diffusely distributed in the cytoplasm of RV-positive fibers. CDK5, CK1δ and JNK were detected only on the rim. In double staining experiments, all GVD markers colocalized with pTDP43 in RVs. These results suggest that RVs of muscle cells and GVD bodies of neurons share a number of molecules, such as raft-related proteins and tau-modifying proteins.